Different textitM’etiers Affect Fish Catches Accounting in Marine Protected Areas: A Pilot Investigation Method - Appolloni, L.; Ciorciaro, D.; Stefano, F. Di; Donnarumma, L.; Ferrigno, F.; Iacono, C.; Miccio, A.; Rendina, F.; Sandulli, R.; Russo, G.F. (Journal of Environmental Accounting and Management, 2026)
The present investigation is a pilot study, carried out in a single season, aiming to account for the effects of local Small-Scale Fishery (SSF) m\’etiers on actual catches, as recommended by the Ecosystem Based Management. According to local m\’etiers, 3 trammel nets (GTR) and 3 longlines (LLS) were hauled for 8 hours in 4 Marine Protected Areas (MPAs) of Campania Region (central Tyrrhenian Sea): Regno di Nettuno (RN) and Punta Campanella (PC), in the northernmost Gulf of Naples, Santa Maria di Castellabate (SMC) and Costa degli Infreschi e della Masseta (CI), along the southernmost coasts of Cilento National Park. PERMANOVA analyses were performed to assess differences in GTR and LLS catches among MPAs; CAP analyses were used to assess similarities among MPAs catches; PERMDISP analyses were performed to verify small scale data homogeneity and comparability; ABCurves were used to assess MPAs fish assemblages quality status. Results show that GTR catches are higher than those of LLS in terms of fish diversity, abundance and biomass. Instead, LLS catches are more selective for a few target species and for larger specimens. PERMANOVA results highlight significant differences of both GTR and LLS data among MPAs, but pair-wise test indicates that LLS catches are more affected by local m\’etiers linked to MPAs environmental characteristics. CAP analyses show that GTR species are coherently correlated with northernmost and southernmost MPAs while, species from LLS are correlated with the morphological characteristics (steep or flat bottoms) of the MPAs. PERMDISP reveals homogeneity among GTR data but not among LLS ones. ABCurves evidence that GTR, due to its low selectivity, is a suitable gear to monitoring MPAs fish assemblage. On the contrary, the high selective of LLS makes it an effective gear to provide data about the main target species of local m\’etiers useful to define more effective MPA management measures.